The role of terrorism in the Cold War (1964-1976) with specific reference to the PLO - Visser, C. J.(Coenraad Johannes) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- Universiteit van Stellenbosch, 1995.